Indonesian Stand-Up Comedy: A New Developing Industry of Youth Culture - Sihombing, Lambok Hermanto; Rahma Fajri, Annisa; Divia Sonali, Mita; Lestari, Puji (Humaniora: Journal of Indonesia Culture and Society, 2023)
The research analyzed the growth of stand-up comedy in Indonesia, which had developed into a new trend or popular culture and a new creative business that produced skilled and well-known comics. Furthermore, it discussed how stand-up comedy might develop into a new creative business by evaluating the growth of the community, Instagram, and YouTube, as well as the growth of successful comics. In order to help the researchers doing the analysis, the researchers applied a qualitative method. They used two theories named Self-presentation concept by Goffman and Creative Industry theory by Richard Florida. The findings indicate that the creative industry does not always progress forward; interest in stand-up comedy decreased in various places, but it is still attempting to develop. Indonesian people are becoming more receptive to stand-up comedy as it is home to some of the world's most talented comics. Comics must be innovative in their approach to content creation to increase their popularity and viability. Apart from that, when comics are popular, they can inspire others to pursue careers as comics. As a result, comics members continue to grow in number, the community grows in size, and the creative business continues to flourish. Stand-up comedy has developed into popular culture and a new creative sector geared toward youth.